(untitled) (Jahangirnagar University Journal of Biological Sciences, 2023)
A pot experiment was conducted to assess the effect of seven different NaCl solution treatments, namely 0, 50, 100, 150, 200, 250 and 300 mM on the growth and yield of BARI Sunflower-2 under sodium chloride stress. Growth parameters such as plant height, leaf number, leaf length, leaf width and leaf area showed a gradual decrease from50 mM to the highest treatment level. Sodium chloride stress caused a significant reduction in early stage growth parameters (15 Days after treatments (DAT), while at 45 DAT the percentages of various growth parameters compared to the control plant at the highest treatment level (300mM) except leaf area. Seed yield per plant and weight of 100 seeds were reduced, respectively by 27.69 and 28.44%at 300 mM salinity, while at moderate salinity (200 mM) seed yield per plant and weight of 100 seed were 83.28 and 84.12%, respectively, as compared to in compared to those of the control plants. The results obtained in the present study showed that the BARI Sunflower-2 cultivar is a moderately salt tolerant plant. Jahangirnagar University J. Biol. Sci. 11(1 & 2): 13-20, 2022 (June & December)